Growth kinetics of ISOVPE HgCdTe epilayers obtained on alloyed CdTe substrates with different crystalline orientations - Gilabert, Ulises Eduardo (2010)
Hg1-xCdxTe (MCT) epilayers were grown on (1 1 1)Cd, (1 1 1)Te, (1 1 0) and (1 0 0) CdZnTe and CdTeSe substrates by isothermal vapor phase epitaxy (ISOVPE). The growth kinetics of the epilayers were studied by a non-linear diffusive convective model for the ISOVPE MCT growth, which was assessed in a previous paper . The non-linear diffusion–convection problem, which describes ISOVPE MCT film growth, was numerically solved by means of discrete mathematics. As the theoretical and experimental composition profiles were remarkably different in accordance with the epilayers grown over pure CdTe substrates, in the model a finite rate in the surface reaction rate constant that enabled a good fit was assumed. The numerical value of the surface reaction rate constant was similar for all the studied substrates and crystalline orientations, hence the results enabled us to determine that the deposition rate has a mixed control for the experimental conditions of this work. This isotropic characteristic of the ISOVPE technique for pure and alloyed CdTe substrates is remarkable, quite different from other MCT growth techniques as MBE or MOCVD.